2002
DOI: 10.1067/mcp.2002.129319
|View full text |Cite
|
Sign up to set email alerts
|

Rifampin markedly decreases plasma concentrations of praziquantel in healthy volunteers

Abstract: Rifampin greatly decreased plasma concentrations of single and multiple oral doses of praziquantel to levels lower than that of the minimum therapeutic concentration. Because praziquantel and rifampin are widely used in the treatment of liver flukes (Opisthorchis viverrini) and Mycobacterium tuberculosis, respectively, in Thailand and in some other countries in southeast Asia, the possibility of one drug influencing the pharmacokinetics of the other must be considered. Therefore simultaneous use of rifampin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 22 publications
(42 reference statements)
1
34
0
1
Order By: Relevance
“…The usual dose of praziquantel is 40 mg/kg in two divided doses; however, in view of its metabolism by hepatic cytochrome P450 enzymes [14,15], any patient who was taking an antiretroviral (ARV) combination that included a P450 enzyme inducer was treated with a dose of 60 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
“…The usual dose of praziquantel is 40 mg/kg in two divided doses; however, in view of its metabolism by hepatic cytochrome P450 enzymes [14,15], any patient who was taking an antiretroviral (ARV) combination that included a P450 enzyme inducer was treated with a dose of 60 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
“…The extraction procedure was carried out according to the methods described by xiao et al (1983) and Ridtitid et al (2002), with some adaptations. Briefly, in a 1.5 mL stoppered microcentrifuge tube, 200 µL of plasma, 25 µL of diazepam (internal standard) solution at 240 µg/mL, 50 µL of 0.2 M zinc sulphate and 300 µL of acetonitrile were vigorously mixed using a vortex mixer for 30 s and then centrifuged at 10,000 g for 10 min.…”
Section: Erythromycin-n-demethylase (End)mentioning
confidence: 99%
“…The concentration of rifampicin was also set at 10 M because it is almost the same as C max of rifampicin after oral administration of 450 to 600 mg in patients with tuberculosis (Smith, 2000). At that dose, interaction of rifampicin with a number of drugs has been reported (Holtbecker et al, 1996;Villikka et al, 1999;Ridtitid et al, 2002). Under these conditions, the effect of MKC-963 on CYP3A4 in the primary culture of human hepatocytes was comparable to the effect of rifampicin, suggesting that MKC-963 is a potent inducer of CYP3A4, similar to rifampicin even in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these drugs are metabolized by CYP3A4 (Li et al, 1995;Lehmann et al, 1998;Prueksaritanont et al, 2003;Jerling et al, 2005), a predominant P450 enzyme found in the adult human liver that catalyzes the oxidation of a wide variety of exogenous compounds (Guengerich et al, 1986). In addition, CYP3A4 had been reported to be induced by several drugs, including rifampicin, phenytoin, and phenobarbital, that caused clinical drugdrug interactions (Holtbecker et al, 1996;Anderson 1998;Ridtitid et al, 2002). Moreover, measurement of the urinary ratio of 6␤-OHF and F (6␤-OHF/F) had been regarded as a safe and simple method for evaluating induction of CYP3A4 because it is noninvasive and does not require administration of a probe drug to volunteers (Galteau and Shamsa, 2003).…”
mentioning
confidence: 99%